Rekayasa Bioteknologi Pertanian Hidroponik Vertikal Dalam Pembelajaran PjBL-Strategi Jigsaw Untuk Meningkatkan Keterampilan Berpikir Kreatif Dan Kreativitas Siswa Kelas X - Dewi Ratna Sari; Ana Permanasari; Dadang Jaenudin (Jurnal Penelitian Pendidikan IPA, 2023)
This study tested the effectiveness of PjBL-STEM learning model jigsaw strategy on creative thinking skills and creativity of grade X students on biotechnology vertical hydroponic farming material. The research method used was quasi-experimental design with pretest-posttest control group design, which was conducted in Class X SMAN 1 Ciracap in Sukabumi Regency as many as 60 students consisting of 30 experimental class students and 30 control class students. Data collection was conducted using initial and final tests for creative thinking skills and observation sheets for student creativity and student response questionnaires to the PjBL-STEM Jigsaw strategy model. Quantitative data from the study were analyzed using SPSS-25 and qualitative data were processed using descriptive analysis. The experimental class received PjBL-STEM learning treatment with jigsaw strategy, while the control class used PjBL. For the first time learning model applied in class X, PjBL-STEM jigsaw strategy is effective in improving students' creative thinking skills and creativity. The prominent creative thinking skills are shown in the fluency and originality indicators. Based on the observation, the implementation of the PjBL-STEM model of jigsaw strategy directs students to the steps of inquiry, engineering design, production process, and communication much better than PjBL.